Analisis Kinerja Portofolio Optimal Menggunakan Model Markowitz pada Instrumen Saham di Bursa Efek Indonesia - Finkan Nadia; Taufiq Kamil Batubara; Bintang Ramadhan Saragih; Nur Hamidah; Dicky Pratama; Tria Annisa; Dinda Aulia Sari; Muhammad Ikhsan Harahap (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the performance and determine the optimal asset allocation of a stock portfolio in the Indonesia Stock Exchange (IDX) by rigorously applying the Markowitz Mean-Variance Model. This research is a quantitative study that utilizes historical return data from a selection of highly liquid blue-chip stocks over a five-year observation period. The methodology involves calculating the expected return, variance, and covariance matrices, followed by quadratic optimization to identify the most efficient portfolios, specifically the Global Minimum Variance Portfolio (GMVP) and the Tangent Portfolio. The findings reveal that significant benefits from diversification are achieved due to moderate positive correlation among the selected assets, resulting in a distinctly curved efficient frontier. The optimal portofolio, characterized by the highest Sharpe Ratio, consistently demonstrates a superior risk-adjusted return profile compared to investing in any single stock asset. This study concludes that the Markowitz Model is highly effective in structuring investment strategies in the IDX, validating the importance of covariance analysis for risk mitigation and strongly aligning with the prudent investment principles of Islamic economics (ghair gharar).